Characterization of PLGA microparticles as a drug carrier for 3-ethoxycarbonyl-2H-benzofuro[3,2-f]-1-benzopyran-2-one. Ultrastructural study of cellular uptake and intracellular distribution - Gomes, Anderson J.; Faustino, Adriana S.; Machado, Antonio Eduardo H.; Zaniquelli, Maria Elisabete D.; de Paula Rigoletto, Thais; Nain Lunardi, Claure; Lunardi, Laurelucia O. (Taylor & Francis Inc, 2006)
Here we describe the application of microparticles (MPs) for the delivery and release of the drug a benzopsoralen. We also evaluated the intracellular distribution and cellular uptake of the drug by using an encapsulation technique for therapeutic optimization. MPs containing the compound 3-ethoxycarbonyl-2H-benzofuro[3,2-f]-1-benzopyran-2-one (psoralen A) were prepared by the solvent evaporation technique, and parameters such as particle size, drug encapsulation efficiency, effect of the encapsulation process on the drug's photochemistry, zeta potential, external morphology, and < i > in vitro release behavior were evaluated. The intracellular distribution of MPs as well as their uptake by tissues were monitored. Size distribution studies using dynamic ligh scattering and scanning electron microscopy revealed that the MPs are spherical in shape with a diameter of 1.4 mu m. They present low tendency toward aggregation, as confirmed by their zeta potential (+10.6 mV). The loading efficiency obtained was 75%. As a consequence of the extremely low diffusivity of the drug in aqueous medium, the drug release profile of the MPs in saline phosphate buffer (pH 7.4) was much slower than that obtained in the biological environment. Among the population of peritoneal phagocytic cells, only macrophages were able to phagocytose poly-d,l-lactic-co-glycolic acid (PLGA) MP. The use of psoralen A in association with ultraviolet light (360 nm) revealed morphological characteristics of cell damage such as cytoplasmic vesiculation, mitochondria condensation, and swelling of both the granular endoplasmatic reticulum and the nuclear membrane. These results indicate that PLGA MP could be a promising delivery system for psoralen in connection with ultraviolet irradiation therapy (PUVA).
Keywords: microparticles; psoralen; PUVA therapy; ultrastructure